Combination of MD simulations with two-state kinetic rate modeling elucidates the chain melting transition of phospholipid bilayers for different hydration levels - Kowalik, Bartosz; Schubert, Thomas; Wada, Hirofumi; Tanaka, Motomu; Netz, Roland R.; Schneck, Emanuel (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2015)
The phase behavior of membrane lipids plays an important role in the formation of functional domains in biological membranes and crucially affects molecular transport through lipid layers, for instance, in the skin. We investigate the thermotropic chain melting transition from the ordered Lβ phase to the disordered Lα phase in membranes composed of dipalmitoylphosphatidylcholine (DPPC) by atomistic molecular dynamics simulations in which the membranes are subject to variable heating rates. We find that the transition is initiated by a localized nucleus and followed by the propagation of the phase boundary. A two-state kinetic rate model allows characterizing the transition state in terms of thermodynamic quantities such as transition state enthalpy and entropy. The extrapolated equilibrium melting temperature increases with reduced membrane hydration and thus in tendency reproduces the experimentally observed dependence on dehydrating osmotic stress.